1999
DOI: 10.1080/088800199277272
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF HYDROXYUREA IN SICKLE CELL ANEMIA: A Clinical Trial in Children and Teenagers with Severe Sickle Cell Anemia and Sickle Cell beta-Thalassemia

Abstract: This study evaluated the efficacy of hydroxyurea treatment in the prevention of vaso-occlusive crises among children and teenagers with severe sickle cell anemia and sickle cell beta-thalassemia. Nineteen children and young adults with severe sickle cell disease were enrolled to the hydroxyurea treatment trial. The incidence of vaso-occlusive crises, acute chest syndrome, hemolytic crises, splenic sequestration episodes, blood transfusions, and hospital days in the 2 years before hydroxyurea (HU) treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 9 publications
2
30
0
3
Order By: Relevance
“…28,29 Bernini et al 28 showed that a 2-day course of intravenous dexamethasone during an ACS episode had a beneficial effect, including a shorter hospital stay, but was complicated by a high readmission rate when compared with the placebo arm. An observational study has reported that albuterol aerosol treatments may improve the clinical status of patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Bernini et al 28 showed that a 2-day course of intravenous dexamethasone during an ACS episode had a beneficial effect, including a shorter hospital stay, but was complicated by a high readmission rate when compared with the placebo arm. An observational study has reported that albuterol aerosol treatments may improve the clinical status of patients with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…50,61,90 Of note, several reports confirm that the effects of hydroxyurea in patients with hemoglobin S/b-thalassemia may be better than those even reported for homozygous hemoglobin S disease, because the synthesized g-chains not only inhibit the sickling process, but they also neutralize the noxious effects of the excess a-chains and cut down on ineffective erythropoiesis. [91][92][93][94][95] Co-inheritance of a-thalassemia was described as a predictor of good response in some studies, 44,77,96 but it was found to have no effect in others. 49,68,85 Homozygosity for the XmnI polymorphism (2158C.…”
Section: Predictors Of Responsementioning
confidence: 99%
“…18 Clinically, hydroxyurea has been shown to decrease the rate of pain and acute chest syndrome (ACS) events in severely affected adults and children. [8][9][10][11]19,20 Organ damage starts very early in life, and most children with SCA lose splenic reticuloendothelial function by 2 years of age. 1 The efficacy of hydroxyurea for the prevention of chronic organ damage in SCA and the potential benefit of dose escalation have not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%